AN ANALYSIS OF THE STUDIES ON THINK TANKS SUCCESS AND RANKING - Özgür, Hüseyin; Kulaç, Onur (European Scientific Journal, ESJ, 2016)
In public policy process; official, unofficial and international actors play complicated roles. As unofficial actors, think tanks contribute to public policy making in various areas and ways and compete with each other. In historical perspective, American think tanks highly beneficial to formulation of internal and foreign policies in their respective country and some of them have noteworthy funding. This study which is structured into three parts starts with the analysis think tanks development and their influence on public policy. Later on, the literature on ranking, success and impact studies of think tanks is intensely scrutinised. Lastly, Global Go To Think Tanks (GGTTT) reports under the leadership of McGann are examined. This study reveals the think tanks ranking literature based on the evolution, citations, similarities and differences of think tanks. Moreover, GGTTT index reports are the most comprehensive, contemporary and prominent of these studies, despite some criticisms made by other scholars and experts.